Sustainable Marketing Management and a Better Sustainable Enterpreunership: North Meruya Community Service Implementation: Sustainable Marketing Management and a Better Sustainable Enterpreunership: North Meruya Community Service Implementation - Mochamad Soelton (Jurnal Abdi Daya, 2024)
MSME economic problems can be overcome by carrying out various MSME-based entrepreneurial activities. Report on the Development of Marketing Planning in Building Beginner Entrepreneurship Based on the Management of Meruya Utara Subdistrict, Kembangan, West Jakarta. This community service aims to assist Marketing Planning in Building Management-Based Entrepreneurship Beginners and benefit from their presence in the online environment. The context of this service involves all functionaries of Meruya Utara Subdistrict, Kembangan, West Jakarta. We will analyze the situation of SMEs, identify opportunities and challenges in marketing culinary products, and develop digital marketing strategies that suit the characteristics of SME products. MSME-based entrepreneurship can be developed to reduce dependence on jobs from companies both government and private. Therefore, even though MSMEs are simpler than general companies, determining a company that will be run by MSMEs must still be done through a clear and concrete process, namely by carrying out a Business Planning process. It is hoped that this community service can provide an understanding of MSME entrepreneurship, so that local people can immediately carry out experiments before trying to determine a business they want to develop in the future. By having an understanding of Business Planning in developing MSME entrepreneurship, it can prevent disagreements and conflicts in the company, so that in the end it can reduce poverty levels and improve community welfare.